Hubungan IPK Sarjana dan Profesi dengan Nilai CBT, OSCE, dan Hasil UKMPPD Di Fakultas Kedokteran Universitas Sam Ratulangi Periode Mei dan Februari 2017 - Febrianti, Winda; Memah, Maya F.; Manoppo, Firginia P. (Universitas Sam Ratulangi, 2017)
Abstract: The average graduation rate of Competency Test for Medical Student Profession Program (UKMPPD) of Sam Ratulangi University (Unsrat) is still below the national average passing rate in the period of May from year 2015 to 2017, as follows: 30.5%, 35.4%, and 36.3% respectively. This study was aimed to determine whether the results of computer based test (CBT), objective structured clinical examination (OSCE), and UKMPPD were correlated with undergraduate and profession grade point average (GPA), which is one of the benchmarks of studentsâ€™ success in their study. This was a quantitative retrospective study with a cross sectional design. The required data were obtained from studentsâ€™ data during education and results of UKMPPD FK Unsrat data (secondary data). The data were analyzed by using Spearman correlation test and Mann Whitney test. Statistical analysis showed that there was a significant correlation (P = 0.001) between undergraduate GPA with CBT (r = 0.770), OSCE (r = 0.544), and UKMPPD results. The professional GPA showed a significant correlation (P = 0.001) with the CBT (r = 0.553), OSCE (r = 0.556), and UKMPD results. Conclusion: There were significant correlations between the undergraduate and professional GPA with the value of CBT, OSCE, and UKMPPD results.Keywords: GPA, CBT, OSCE, UKMPPDÂ Abstrak: Rerata angka kelulusan Uji Kompetensi Mahasiswa Program Profesi Dokter (UKMPPD) Universitas Sam Ratulangi (Unsrat) masih di bawah rerata angka kelulusan nasional yaitu secara berturut-turut dari tahun 2015 sampai tahun 2017 periode Mei, 30,5%, 35,4%, dan 36,3%. Penelitian ini bertujuan untuk mengetahui apakah nilai computer based test (CBT), objective structured clinical examination (OSCE), maupun hasil UKMPPD memiliki hubungan dengan nilai indeks prestasi kumulatif (IPK) sarjana dan profesi, yang menjadi salah satu tolok ukur keberhasilan seorang mahasiswa dalam pendidikan. Jenis penelitian ialah kuantitatif retrospektif dengan desain potong lintang. Data penelitian diperoleh dari data sekunder berupa data mahasiswa selama menempuh pendidikan dan data hasil UKMPPD FK Unsrat. Data dianalisis menggunakan uji korelasi Spearman dan uji Mann Whitney. Hasil penelitian mendapatkan hubungan bermakna (P=0,001) antara IPK sarjana dengan nilai CBT (r=0,770), nilai OSCE (r=0,544), dan hasil UKMPPD; serta hubungan bermakna (P=0,001) antara IPK profesi dengan nilai CBT (r=0,553), OSCE (r=0,556), dan hasil UKMPPD. Simpulan: Terdapat hubungan bermakna dari IPK sarjana dan profesi dengan nilai CBT, OSCE, dan hasil UKMPPD.Kata kunci: IPK, CBT, OSCE, UKMPPD